DETEKSI KECURANGAN LAPORAN KEUANGAN MODEL FRAUD HEXAGON (STUDI KASUS PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BEI PERIODE 2020-2022) - Lanang Surya Ramadhan; Kurnia Rina Ariani (Jurnal Akuntansi dan Pajak, 2024)
Financial reports are a benchmark for the financial condition of a company. So, even a small amount of fraud in financial reports has quite a big impact on the reliability of the financial reports. Fraud problems occur due to opportunities, gaps, and weak supervision in a company. Fraud in financial reports by examining it in more depth. of the factors that influence fraud, Vausinas calls his model the Hexagon Fraud or abbreviated as SCCORE (Stimulus, Collusion, Competency, Opportunity, Rationalization, and Ego). Fraud hexagon theory is a development of the previous fraud theory introduced in Vousinas (2019) by adding a new component, namely collusion. This research uses 10 variables. The dependent variable in this research is financial statement fraud, while the independent variables are external pressure, financial stability, financial targets, nature of the industry, monitoring ineffectiveness, change of auditor, change of directors, number of CEO photos, and cooperation with the government. This research was conducted using secondary data obtained from the financial reports of basic industrial and chemical companies listed on the Indonesia Stock Exchange from 2020 to 2022. This data was obtained by accessing the official website of the Indonesian Stock Exchange (BEI), namely www.idx.co.id and the official website of each company. The test results show that external pressure, financial stability and the nature of the industry are accepted. Meanwhile, other variables are rejected